2019
DOI: 10.1136/bmjhci-2019-100015
|View full text |Cite
|
Sign up to set email alerts
|

Availability and usage of clinical decision support systems (CDSSs) in office-based primary care settings in the USA

Abstract: BackgroundA clinical decision support system (CDSS) covers a broad spectrum of applications, for example, screening reminders, can reduce malpractice, improve preventive services and enable better management of chronic conditions. CDSSs have traditionally been used successfully in large hospitals. The availability (ie, whether the function is provided by the software) and usage (ie, actual use) of a CDSS in office-based primary care settings, however, are less well studied.ObjectiveTo establish a benchmark of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…However, meta-analyses of CDS intervention studies show substantial heterogeneity in effect sizes [ 8 10 ]. Furthermore, widespread adoption of CDS systems has not been achieved [ 13 ], and access to CDS does not guarantee user uptake or acceptance in clinical settings [ 14 16 ]. For example, a review of 23 studies examining medication CDS systems found that between 46 and 96% of medication alerts were overridden by clinicians [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, meta-analyses of CDS intervention studies show substantial heterogeneity in effect sizes [ 8 10 ]. Furthermore, widespread adoption of CDS systems has not been achieved [ 13 ], and access to CDS does not guarantee user uptake or acceptance in clinical settings [ 14 16 ]. For example, a review of 23 studies examining medication CDS systems found that between 46 and 96% of medication alerts were overridden by clinicians [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…CDSS has been recognized and adopted broadly in healthcare settings due to its effectiveness in improving healthcare quality, adherence rates in medication prescription, and other clinical orders [13,14]. CDSS is usually a part of an electronic health record system.…”
Section: Cdss Ontologymentioning
confidence: 99%
“…Se observó una baja utilización del algoritmo de ajuste oferta/demanda, fenómeno que ha sido descrito con una amplia variabilidad de adherencia en otras herramientas de soporte al razonamiento clínico y que requieren un proceso de alfabetización digital para los equipos decisores 8 .…”
Section: Conclusionesunclassified